K-Pop and Education Migration to Korea in the Digitalised COVID-19 Era - Sunghyun Park; Storm Schutte; Sungwoo Park (Social Sciences)
This study examines the relationship between K-Pop and education migration to South Korea in the context of the global internet and the COVID-19 pandemic. It focuses on the phenomenon in which local Asian territories have been widely influenced by the Korean Wave, particularly K-Pop, even during the era of global communication and health risks. This research illuminates some intriguing aspects of the distinctive reception patterns of Korean Wave audiences, as well as their unique characteristics, such as innocence, transgression, and the nuanced dynamics of the fandom during that period. Furthermore, this research engages critically with controversial aspects of cultural politics, such as the transmission of the legacy of K-Pop and the centralisation of femininity more actively. This study concludes that K-Pop has recently been relocated to the conjunctures of mediated and overdetermined influences on students’ education migration to South Korea rather than acting as a direct power and reason for it, particularly in the context of the COVID-19 pandemic and the rapid digitalisation of education.